Long-term outcome of patients with nonspecific pleurisy at medical thoracoscopy. (March 2017) - Yang, Yuan; Wu, Yan-Bing; Wang, Zhen; Wang, Xiao-Juan; Xu, Li-Li; Tong, Zhao-Hui; Shi, Huan-Zhong
Abstract: Background: Medical thoracoscopy is an effective and safe procedure for diagnosing pleural effusions of undetermined causes. But there are still a part of patients with pleural effusions were diagnosed as nonspecific pleurisy when no specific biopsy results were found after undergoing thoracoscopic biopsy. The long-term outcome of these patients is unclear, and anxieties about undiagnosed malignancy persist. Methods: Between July 2005 and June 2014, medical thoracoscopy using the semi-rigid instrument was performed and pleural biopsy was taken in 833 patients with pleural effusions. Fifty-two patients diagnosed with nonspecific pleurisy with available follow-up data were included in the present study and their medical records were reviewed. Results: Fifty-two patients (31 men and 21 women) were included. Mean follow up was 35.5 ± 40.9 months (range, 1–143 months). No specific diagnosis was established in 21 (40.4%) of the patients. Eight of 52 patients with nonspecific pleurisy (15.4%) were subsequently diagnosed with pleural malignancies. 23 of 52 patients (44.2%) were diagnosed as benign diseases. The recurrence of pleural effusion during followed-up and pleural nodules or plaques found in medical thoracoscopy was associated with malignant disease. Conclusion: Patients with nonspecific pleurisy after medical thoracoscopy should be closely monitored, especially in those patients with the recurrence of pleural effusion during followed-up, pleural nodules or plaques found in medical thoracoscopy. One year of clinical follow-up for patients found to have nonspecific pleurisy is likely sufficient. Highlights: Patients with diagnosis of nonspecific pleurisy should be closely monitored. The recurrence of pleural effusion was more frequent in ultimate pleural malignancy. Pleural nodules and plaques were more frequent in ultimate pleural malignancy. One year of follow-up for nonspecific pleurisy patients is likely sufficient.